2003
DOI: 10.1038/nature01508
|View full text |Cite
|
Sign up to set email alerts
|

An energetic stellar outburst accompanied by circumstellar light echoes

Abstract: Some classes of stars, including supernovae and novae, undergo explosive outbursts that eject stellar material into space. In 2002, the previously unknown variable star V838 Monocerotis brightened suddenly by a factor of about 10^4. Unlike a supernova or nova, V838 Mon did not explosively eject its outer layers; rather, it simply expanded to become a cool supergiant with a moderate-velocity stellar wind. Superluminal light echoes were discovered as light from the outburst propagated into surrounding, pre-exist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
274
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(290 citation statements)
references
References 18 publications
13
274
3
Order By: Relevance
“…Our derived A V is considerably higher than those reported for about the same time period by Kimeswenger et al (2002), who found A V ¼ 1:8 and 2.4, respectively. An A V this large is almost certainly due to extinction from dust near the source from the present outburst or perhaps from some of the dust evident in the HST light-echo images (Bond et al 2003). Indeed, the progenitor of V838 Mon was detected in 1983-1984 as IRAS 07015À0346.…”
Section: The Late Spectrum (2002 December-2003 January)mentioning
confidence: 99%
See 2 more Smart Citations
“…Our derived A V is considerably higher than those reported for about the same time period by Kimeswenger et al (2002), who found A V ¼ 1:8 and 2.4, respectively. An A V this large is almost certainly due to extinction from dust near the source from the present outburst or perhaps from some of the dust evident in the HST light-echo images (Bond et al 2003). Indeed, the progenitor of V838 Mon was detected in 1983-1984 as IRAS 07015À0346.…”
Section: The Late Spectrum (2002 December-2003 January)mentioning
confidence: 99%
“…Soker & Tylenda (2003) proposed a stellar merging event (see also Kato 2003), but this would seem untenable in view of the apparent recurrent ejection episodes evidenced by the HST imagery (Bond et al 2003). The similarities between V838 Mon's behavior and that of M31 RV (Rich et al 1989), V4334 Sgr (Evans, Smalley, & Kimeswenger 2002), and V4332 Sgr (Martini et al 1999) have been noted by several groups (Wagner et al 2002b;Kimeswenger et al 2002;Munari et al 2002b;Bond et al 2003). Retter & Marom (2003) suggest that the object's observed behavior could be explained by an expanding central red giant that enveloped three relatively massive planets in close orbits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powerful outburst of V838 Mon in 2002 (Munari et al 2002), accompanied by a spectacular light echo (Bond et al 2003), raised interest in a class of stellar eruptions named "red novae", "optical transients" or "V838 Mon type eruptions". These objects, which typically reach a maximum luminosity of ∼10 6 L , evolve to low effective temperatures and decline as Based on observations obtained with the 1.3-m Warsaw telescope at the Las Campanas Observatory of the Carnegie Institution of Washington.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-epoch images of the echo show a diffuse nebula surrounding the star that exhibits a complex morphology (Bond et al 2003;Carlqvist 2005). Polarimetric observations of the echo were used to derive a geometric distance of 6 kpc (Sparks et al 2008).…”
Section: Introductionmentioning
confidence: 99%